2021
DOI: 10.1071/fp21243
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative and quantitative analyses of the plasmodesmata that accompany cell fate changes during the somatic embryogenesis of

Abstract: Plasmodesmata (PD) are cytoplasmic and membrane-lined microchannels that enable symplasmic communication in plants, which is involved in the regulation of cell differentiation. The presented results emphasise the qualitative and quantitative analyses of PD, which are the basis of the symplasmic communication. The cells that initiate various development programmes create symplasmic domains that are characterised by different degrees of symplasmic communication. Changes in symplasmic communication are caused by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…Symplasmic domains were determined for embryogenesis [ 66 , 81 , 82 , 83 , 84 ], androgenesis [ 85 ], and somatic embryogenesis [ 67 , 86 , 87 , 88 , 89 , 90 ].…”
Section: Symplasmic Isolation As a Mechanism Controlling Somatic Embr...mentioning
confidence: 99%
See 3 more Smart Citations
“…Symplasmic domains were determined for embryogenesis [ 66 , 81 , 82 , 83 , 84 ], androgenesis [ 85 ], and somatic embryogenesis [ 67 , 86 , 87 , 88 , 89 , 90 ].…”
Section: Symplasmic Isolation As a Mechanism Controlling Somatic Embr...mentioning
confidence: 99%
“…The correlation between symplasmic domains and zygotic embryo development has been described for Arabidopsis and Sedum [ 66 , 82 , 83 , 88 , 89 ]. Studies on Arabidopsis showed that the zygotic embryo is a single symplasmic domain during all stages of development, but only for low molecular weight molecules (up to 0,5 kDa).…”
Section: Symplasmic Isolation As a Mechanism Controlling Somatic Embr...mentioning
confidence: 99%
See 2 more Smart Citations